Microbial Hazards of Street-Vended Grilled Chicken Intestine - Azanza, Ma. Patricia; Gedaria, Arlyn (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Microbial hazards associated with street-vended grilled chicken intestine ( isaw ) were studied. Grilling of isaw effected ≥89.00% decrease in the total microbial load of the sample. Cooked isaw contained about 10 5 -10 6 cfu/g aerobic plate counts and 10 3 -10 4 MPN/g coliform counts. Salmonella per 25 g sample was isolated from cooked isaw samples. Grilling eliminated Staphylococcus aureus and Listeria monocytogenes cells initially present in pre-cooked samples. Different sauces of isaw showed increasing numbers of total aerobic microorganisms and coliform during vending operations. The total plate counts and coliform counts of the sour sauce, which ranged from 10 3 -10 5 cfu/g and 10 1 MPN/g, respectively, were observed to be lower than those found in the sweet sauce. Sources of microbial contaminants of grilled chicken isaw included the natural flora of the raw materials, contaminations from food-contact surfaces, bamboo skewers, and the hands of the food handlers. Among the critical control points identified in the street-vending operation of chicken isaw were the control of time and temperature during cooking and hold-on periods during vending operations.
Keywords: microbial hazards; streetfood; HACCP